Communication Regime in Telematic Media - Mondaca Miranda, Alexis; Díaz Pantoja, Juliana Salome; Lucero Pantoja, Jairo Enrique (Law, State and Telecommunications Review, 2023)
[Purpose] To analyze and determine the impact of telematic media on the exercise of the communication regime between children and adolescents and their parents, with emphasis on the transformation generated by the mobility restrictions derived from Covid-19. [Methodology/Approach/Design] For the development of this work, a descriptive and explanatory research is used, employing the dogmatic methodology -classical of the legal sciences- and the systematic, analytical and factual sub-methods. [Findings] Based on the present work, it is evident that: (i) effective compliance with the communicational regime cannot be understood exclusively from a physical visitation mechanism; (ii) telematics resources have allowed the communicational regime through physical visits to be complemented as well as perfected; (iii) there is a normative diaspora at the international level - with greater force after the pandemic - that tries to regulate virtual interaction in the compliance of communicational regimes, however it is not possible to define a majority position that resolves its treatment, although physical contact is still considered as a necessary source to guarantee the family unity of the child and adolescent. [Practical Implications] This article critically emphasizes two points: (i) the normative dispersion with respect to the regulation of telematics media as formulas for compliance of the communication regime; consequently, (ii) it is necessary to carry out an interdisciplinary analysis to determine to what degree the new technologies allow the generation of the affective bond required by the communication regime, and to which children and adolescents and their parents have a right. [Originality/Value] The present research is novel given the post-pandemic context in which the need to incorporate telematic media in the communication regime must be verified, as well as the opportunity to anticipate future scenarios that may again generate isolation measures.